2023
DOI: 10.3389/fendo.2023.1134065
|View full text |Cite
|
Sign up to set email alerts
|

Association between weight-adjusted waist index and arterial stiffness in hypertensive patients: The China H-type hypertension registry study

Abstract: ObjectiveExploring the relationship between (weight-adjusted waist index) WWI and arterial stiffness (AS) in the total and different BMI populations among patients with hypertension.MethodsThis study enrolled 5232 hypertensive subjects, a subset of the China H-type Hypertension Registry Study. WWI was calculated as WC (cm) divided by the square root of weight (kg). Brachial-ankle pulse wave velocity (baPWV) was measured to determine AS.ResultsThe mean WWI was 10.97 (0.78)cm/√kg. In multiple logistic analyses s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 32 publications
(22 reference statements)
0
0
0
Order By: Relevance
“…Due to ethnicities, cultural differences, diet habits, genetic variances, and lifestyle factors between Chinese and American older adults populations, we found that WWI among older adults hypertensive patients in the United States was notably greater than Showcases the results of a subgroup analysis that focuses on the correlation between the prevalence of hypertension in older adults individuals and WWI. (34). Thus, these differences may explain the discrepancy in findings between our study and the Rural Chinese Cohort Study.…”
Section: Comparison With Previous Studiescontrasting
confidence: 72%
“…Due to ethnicities, cultural differences, diet habits, genetic variances, and lifestyle factors between Chinese and American older adults populations, we found that WWI among older adults hypertensive patients in the United States was notably greater than Showcases the results of a subgroup analysis that focuses on the correlation between the prevalence of hypertension in older adults individuals and WWI. (34). Thus, these differences may explain the discrepancy in findings between our study and the Rural Chinese Cohort Study.…”
Section: Comparison With Previous Studiescontrasting
confidence: 72%
“…This suggests that WWI could be a valuable factor in managing arterial stiffness, alongside blood pressure control, to mitigate the risk of future CVD events. 22 Additionally, WWI’s reliability extends to predicting stroke subtypes of CVD, where a significant relationship between higher WWI levels and increased stroke incidence was observed. 19 The unique focus of our study was on evaluating the impact of the WWI on CVD risk in patients with hypertension and OSA.…”
Section: Discussionmentioning
confidence: 99%
“…Our study is basically consistent with previous studies, indicating a significant positive correlation between central visceral obesity, as measured by the WWI, and CVD along with its subtypes. 18 , 19 , 22 , 25 Specifically, a national cohort study in South Korea demonstrated that WWI is a superior predictor of CVD mortality compared to BMI, WC, and WHtR, highlighting its predictive power. 18 Furthermore, WWI is strongly associated with arterial stiffness, a known risk factor for CVD.…”
Section: Discussionmentioning
confidence: 99%